2020
DOI: 10.1111/trf.15737
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CD36 deficiency in Thais analyzed by quantification of CD36 on cell surfaces and in plasma

Abstract: BACKGROUND Anti‐CD36s, developing after transfusion or during pregnancy, play an important role in immune‐mediated bleeding disorders among Asian populations. Currently, little is known about the clinical relevance of anti‐CD36. Here, we aimed to determine the frequency of CD36 deficiency in Thais by analyzing CD36 expression on cell surfaces and in plasma. STUDY DESIGN AND METHODS The expression and deficiency of CD36 on platelets and monocytes were determined by flow cytometry. Mutations in the CD36 gene wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Frequently observed were CD36*c.268C > T , c.329_330delAC, c.ins949A, c.1228‐1239del12 , and others. Most mutations observed in this study differ from the reported variations, except for CD36*c.975 T > G (p.Y325X), 30 c.1079 T > G (p.L360X), 31 c.1156C > T (p.R386W), 15,17 and IVS12, 1200‐53_‐5inv49 26 indicating that CD36 variation in individuals from Arabian countries seems to have developed largely independent from those in Eastern Asia. The CD36*c.1079 T > G variation has been described before as a very rare mutation in a Caucasian pedigree presenting with autosomal dominant diabetes 31 .…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Frequently observed were CD36*c.268C > T , c.329_330delAC, c.ins949A, c.1228‐1239del12 , and others. Most mutations observed in this study differ from the reported variations, except for CD36*c.975 T > G (p.Y325X), 30 c.1079 T > G (p.L360X), 31 c.1156C > T (p.R386W), 15,17 and IVS12, 1200‐53_‐5inv49 26 indicating that CD36 variation in individuals from Arabian countries seems to have developed largely independent from those in Eastern Asia. The CD36*c.1079 T > G variation has been described before as a very rare mutation in a Caucasian pedigree presenting with autosomal dominant diabetes 31 .…”
Section: Discussioncontrasting
confidence: 78%
“…Different mutations within the coding region, 5'UTR and an unusual complex molecular regulation of CD36 in different tissues have been addressed as basis of this peculiar expression. Since the first descriptions, a high number of different mutations associated with a negative or weak phenotype has been reported, most of them in Eastern Asians 11,15–18,26,28,29 . Frequently observed were CD36*c.268C > T , c.329_330delAC, c.ins949A, c.1228‐1239del12 , and others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation